Long COVID: Diagnosis and Treatment of Respiratory Syndrome in Post COVID-19 Conditions - Erlina Burhan (Jurnal Respirologi Indonesia, 2022)
The ongoing COVID-19 pandemic has given rise to another medical burden that came from the symptoms experienced by patients after acute infection with SARS-CoV-2, a condition often called as Long COVID. As the number of COVID-19 cases remain rising, various studies and scientific researches are being conducted to understand more about Long COVID, and findings have consistently shown increased burden due to Long COVID that needs more attention from the clinical world. This article review collects various sources regarding the diagnosis and management of respiratory syndrome in post-COVID-19 conditions. Long COVID, currently referred to as a post-COVID-19 condition, consists of symptom(s) that occurs in individuals with a history of probable or confirmed SARS-CoV-2 infection, with symptoms lasting at least two months and cannot be explained by any alternative diagnosis. Symptoms that occur are very diverse from various organ systems, including the respiratory system. Knowledge regarding the possible symptoms as well as a thorough evaluation is needed to identify and diagnose post-COVID-19 conditions, and multidisciplinary management through a tiered system may help reach more cases of post-COVID-19 conditions. The treatment for post-COVID-19 conditions needs to be adjusted to the patient's condition, and the administration of pharmacological therapy such as steroids, bronchodilators, and mucolytics/antioxidants has to be based on clinical symptoms and radiological abnormalities.